Přehled atmosférických nosičů pro vypouštění družic na oběžnou dráhu Země - Bačová, Alena (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Tahle bakalářská práce je rešerší zabývající se přehledem atmosférických nosičů pro vypouštění družic na oběžnou dráhu Země. Práce je rozdělena do čtyř hlavních částí. V první se zabývá základními principy reaktivního pohonu a jeho dvěma typům motoru. Ve druhé části je zpracován přehled atmosférických nosičů v USA. Třetí část se zabývá atmosférickými nosiči v bývalém SSSR. Čtvrtá část je věnována atmosférickým nosičům v Evropě.

This bachelor´s thesis is dealing with an overview of aircrafts designed as a launch platform for an air launch of satellite into the low Earth orbit. The thesis is divided into four main parts. The first part describes main principles of reaction engine and its two types of engines. The second part provides an overview of aircrafts as launch platform in the USA. The third part deals with these launch platforms in the former SSSR. The fourth part is devoted to aircrafts as launch platform in the Europe.
An overview of atmospheric carriers for launching satellites into Earth's orbit
Keywords: Kosmonautika; atmosférické nosiče; nosná raketa; družice; vzdušný start; Cosmonautics; launch platform; launch vehicle; satellite; air launch to orbit